African mythology A to Z - Lynch, Patricia Ann. (New York Facts on File, 2004)
Designed specifically for young readers, the Mythology A to Z series explores the world's most important myths and legends in an accessible and entertaining manner. Each volume includes vividly written entries on the major figures, places, stories, objects, and themes of a given mythology. A vast continent, Africa is the home of the first humans and the birthplace of many cultures, ranging from nomadic bands to farmers to sophisticated civilizations. With four major language families and myriad peoples, Africa is also the source of a diverse and engaging body of myth. African Mythology A to Z is a clearly written reference guide to this lore. Containing 42 illustrations, two maps, a time line, a bibliography, an index, and extensive cross-references, African Mythology A to Z is a comprehensive and accessible reference guide for anyone interested in learning more about various African myths, traditions, and beliefs
Acknowledgments -- Introduction -- Map of modern Africa -- Countries and tribal regions -- Time line of African history -- A-to-Z Entries -- Selected bibliography -- Index
Floyd Dickman Children's Literature Collection. 5O
Includes bibliographical references (pages 127-129) and index
Keywords: Mythology, African -- Encyclopedias, Juvenile